Surviving the Legacy Media System: The Place of Local Digital Activism in the Chiloé Red Tide Crisis - Broitman-Rojas, C; Jara-Reyes, R (Palgrave Macmillan, 2020)
In the summer of 2016, Chile experienced a red tide phenomenon. News of the red tide spread quickly through local, national and global media, accompanied by photos of beaches strewn with dead marine life that had ingested the algae. Chiloé Island, in the south of Chile, was particularly impacted by the red tide, triggering a crisis for the local salmon farming industry and fishing industry more broadly. At the time, the relations between the red tide and the dumping of farmed salmon were the subject of much controversy and conflict with suggestions that the salmon industry had caused the red tide. In this chapter, we examine the role of local activists in the diffusion of this socio-environmental controversy about the origins of the red tide phenomenon. While legacy media preferred official interpretations, social media fostered dissident voices that challenged trust in government and scientific expertise. Existing literature usually identifies how activists use social media but less evidence is available on how activists proceed in sustaining environmental communication over time. Through a targeted analysis of three Facebook fan pages, the study maps the trajectory of the activists’ environmental communication and how their efforts survived the controversy through temporal and strategic use of social media. © 2020, The Author(s).